Role of cpxA Mutations in the Resistance to Aminoglycosides and β-Lactams in Salmonella enterica serovar Typhimurium - Jing, Wenxian; Liu, Juan; Wu, Shanshan; Li, Xuerui; Liu, Yongsheng (Frontiers in Microbiology, 2021)
Although it has been reported that deletion of the response regulator, CpxR, in the CpxRA system confers sensitivity to aminoglycosides (AGAs) and β-lactams in Salmonella enterica serovar Typhimurium, the regulatory effects of CpxA on multidrug resistance (MDR) are yet to be fully investigated in this organism. Here, to explore the role of CpxA in MDR, various cpxA mutants including a null mutant (JSΔcpxA), a site-directed mutant (JSΔcpxA38) and an internal in-frame deletion mutant (JSΔcpxA92–104) of the S. enterica serovar Typhimurium strain JS, were constructed. It was revealed that cpxA and cpxR deletion mutants have opposing roles in the regulation of resistance to AGAs and β-lactams. Amikacin and cefuroxime can activate the CpxRA system, which results in increased resistance of the wild-type compared with the cpxR deletion mutant. All the cpxA mutations significantly increased resistance to AGAs and β-lactams due to CpxRA system activation via the phosphorylation of CpxR. Moreover, AckA-Pta-dependent activation of CpxR increased the antibiotic resistance of cpxA deletion mutants. Further research revealed that the AcrAB-TolC conferred resistance to some AGAs and β-lactams but does not influence the regulation of resistance by CpxRA against these antibiotics. The detection of candidate MDR-related CpxR regulons revealed that the mRNA expression levels of spy, ycca, ppia, htpX, stm3031, and acrD were upregulated and that of ompW was downregulated in various cpxA mutants. Furthermore, the expression levels of nuoA and sdhC mRNAs were downregulated only in JSΔcpxA92–104. These results suggested that cpxA mutations contribute to AGAs and β-lactams resistance, which is dependent on CpxR.